Spatio-temporal modelling of land use/land cover and climate change effects on surface runoff and river discharge in the Klang River basin - Azari, Majid (2024)
Urbanisation, climate change, and their impacts on hydrological processes are a growing concern in urban watersheds around the world. This research examined the complex relationship between land use and land cover (LULC) change, precipitation variability, and their combined spatio-temporal impacts on surface runoff and river discharge in the Klang River basin, Malaysia.